PTU-100 Efficacy of obeticholic acid treatment in patients with primary biliary cholangitis with cirrhosis. (17th June 2017) - Vierling, JM; Hirschfield, G; Jones, DE; Groszmann, R; Kowdley, KV; Pencek, R; Marmon, T; MacConell, L
Abstract : Introduction: Obeticholic acid (OCA) is a potent and selective farnesoid X receptor (FXR) agonist under investigation for treatment of primary biliary cholangitis (PBC) and other chronic liver diseases. POISE was a double-blind, placebo-controlled, randomised Phase 3 study examining the efficacy of OCA in PBC. The objective of this post-hoc analysis was to assess the efficacy of OCA in the subset of patients with cirrhosis who were at higher risk of progression to liver-related outcomes or death. Method: We randomised and dosed 216 patients 1:1:1 with placebo (PBO) (n=73), OCA 5–10 mg (n=70, titrated to 10 mg after 6 months based on response and tolerability) or OCA 10 mg (n=73). Inclusion criteria included PBC diagnosis, ALP≥1.67x ULN and/or total bilirubin (BILI) >ULN to <2x ULN, stable UDCA dose or intolerance to UDCA. Patients were considered to have cirrhosis if they met one of the following criteria: biopsy-proven cirrhosis, transient elastography of ≥16.9 kPa, or history of cirrhosis. The primary composite endpoint was an ALP<1.67x ULN with ≥15% reduction in ALP and BILI ≤ULN after 12 months. Results: Cirrhosis was present in approximately 17% of patients in POISE: PBO, n=13; OCA 5–10 mg, n=13; OCA 10 mg, n=10. At month 12, 54% (p<0.05) of patients in the OCA 5–10 mg group and 40% (p=0.06) in the OCA 10 mg group met the primary composite endpoint compared to 8% of PBO patients with cirrhosis. The table shows significant differences in ALP and BILI between PBO and both OCA groups after 12 months. BILI increased on PBO; however, it remained stable in both OCA groups after 12 months of treatment. Pruritus was the most common adverse event in patients with cirrhosis, affecting 23%, 69%, and 80% of patients in the PBO, OCA 5–10 mg, and OCA 10 mg groups, respectively. Conclusion: In this post-hoc analysis, no additional safety concerns due to OCA were observed in the subgroup of OCA-treated patients with cirrhosis, and OCA treatment resulted in significant improvements in biochemical markers associated with disease progression. The percentage of patients achieving the primary composite endpoint on OCA was comparable in patients with cirrhosis and non-cirrhotic patients. These results suggest that OCA may play a beneficial role in preservation of the functional capacity of residual liver tissue in cirrhotic patients. Disclosure of Interest: J Vierling: None Declared, G. Hirschfield: None Declared, D. Jones: None Declared, R. Groszmann: None Declared, K. Kowdley: None Declared, R. Pencek Conflict with: Intercept Pharmaceuticals, Inc., Conflict with: Intercept Pharmaceuticals, Inc., T. Marmon Conflict with: Intercept Pharmaceuticals, Inc., Conflict with: Intercept Pharmaceuticals, Inc., L. MacConell Conflict with: Intercept Pharmaceuticals, Inc., Conflict with: Intercept Pharmaceuticals, Inc.